Application of Ice Gel For Edible Flowers Distribution Packaging of Butterfly Pea - Ulya, Kamila Nikmatul; Darmawati, Emmy; Wulandani, Dyah (Jurnal Keteknikan Pertanian, 2024)
Butterfly pea (Clitoria ternatea) is a popular edible flower in Indonesia that is rich in antioxidants. However, they are perishable and sensitive to temperature changes during storage and transportation. The use of ice gel in distribution packaging has been identified as an effective solution to maintain its quality. This study aimed to determine the optimal positioning of ice gel in two types of distribution packaging: a Styrofoam box and an insulated box. The experiment involved cooling 36 g of flowers per distribution package over 2 h of simulation using six pieces of ice gel at two different positions (positions 1 and 2). The results showed that the ice gel placed in position 2 reduced the temperature inside the packaging more rapidly and maintained the lowest temperature for a longer period than the ice gel placed in position 1. Therefore, placing the ice gel in position 2 is the best option for application in the distribution package. Ice gel position 2 can reduce the flower’s temperature from 20°C to 10.7°C in the Styrofoam box and from 20oC to 11°C in the insulated box during simulation.